Facile fabrication of silver nanoparticle-coated silica-C18 core–shell microspheres and their applications in SERS detection. Issue 31 (31st March 2017) - Xue, Lin; Gu, Hai-Xin; Yuan, Shou-Qi; Li, Da-Wei
Abstract : We present a one-step method to prepare silver nanoparticle (Ag NP) shell coated functional microspheres as a surface-enhanced Raman scattering (SERS) substrate. Abstract : We present a one-step method to prepare silver nanoparticle (Ag NP) shell coated functional microspheres as a surface-enhanced Raman scattering (SERS) substrate. The microspheres, linked by n -octadecane chains, were bonded and covered by aggregations of Ag NPs. The process of the coverage of Ag NPs on a microsphere surface was investigated by scanning electron microscopy, and the SERS activity was optimized using rhodamine 6G as a probe molecule. This spatial structure composed of inner n -octadecane chains and an outer coarse silver shell achieved dual functionality of molecule adsorption and sensing, due to its capacity to capture analytes with alkyl chains, thus achieving effective SERS detection with bare compacted Ag NPs. The SERS detection of low concentrations of 2.6 × 10 −7 M, 2.5 × 10 −8 M and 5.4 × 10 −8 M could be achieved for naphthalene, 2, 6-dimethylnaphthalene, and 1-naphthol, respectively. The prepared Ag NP shell composite microspheres would expand the range of applications for SERS, and provide an effective method for the quick SERS detection of poor-SERS-responsive molecules.